Design of an elevator group supervisory controller using ordinal structure fuzzy logic with context adaptation - Danapalasingam, Kumeresan A.; Khalid, Marzuki (2005)
An elevator group supervisory controller is a control system that manages systematically two or more elevators in order to serve passengers as required. The elevator cars are assigned accordingly in response to hall calls, so as to optimize waiting time, riding time, power consumption, passengers’ comfort, etc. In this paper, the simplicity of ordinal structure fuzzy logic in making crucial supervisory control decisions is demonstrated. In addition, in order to further improve the performance, a new approach of ordinal structure fuzzy logic with context adaptation is demonstrated to implement an elevator group supervisory controller for a building with 15 floors and 4 elevator cars. Simulations comparing ordinal structure fuzzy logic algorithm with and without context adaptation, show that the former performs better